Discourse of copywriting on Malaysian celebrity television advertisement - Roslan, Nur Widad (2018)
Copywriting is the text created by copywriters to promote products. However, lack of creativity and awareness from the copywriters created a negative acceptance from viewers and listeners. Therefore, this study is to identify the elements of critical discourse according to Fairclough (1995) in copywriting on Malaysian celebrity television advertisement and to analyse the impact of the element of critical discourse in copywriting on Malaysian celebrity television advertisement towards consumers. The samples of this study were 60 Malaysian celebrity television advertisements and 35 male and female students from University Putra Malaysia. The instruments of this study involve video observation and an interview. Malaysian television advertisements using Malaysian celebrity endorser are observed while the subjects are interviewed with a set of questions pertaining to their perception towards elements of critical discourse in Malaysian celebrity television advertisement. The video observation data is analysed through the first dimensions of critical discourse which is the textual analysis, while the answer from the interview are analysed on the second dimension which is discourse practice analysis. The results of the study revealed that the copies in advertisement have most of the elements from Fairclough (1995) theory. The results also revealed the subjects’ perceptions towards critical discourse in Malaysian celebrity television advertisement are important and are needed in television advertisement in order to have full understanding of the message. The overall results of this study show support towards Fairclough (1995) critical discourse analysis and his two out of three dimensions of discourse that was present for both the objectives in the study. It is hoped that this study helps copywriters in Malaysia with quality wiring in their copies, increase product owner’s knowledge on a quality copy for television advertisement.